Residential Segregation by Skin Color in Brazil - Telles, Edward E. (American Sociological Review, 1992)
I examine residential segregation by skin color in 35 of the largest metropolitan areas in Brazil, using census tract data from the 1980 Brazilian census. Residential dissimilarity among whites, mulattoes (browns) and blacks is only moderate by U.S. standards. White-black dissimilarity is the highest, followed by brown-black and then white-brown dissimilarity. Residential segregation within income groups is lowest for the low income groups and increases with increasing income level. For most of the white middle class, residential separation is ensured by the concentration of blacks and mulattoes in low socioeconomic classes and in distinct regions. Multivariate analysis reveals that an urban area's socioeconomic status and housing market are strong predictors of overall residential segregation : segregation is significantly higher in urban areas with high occupational inequality, low mean income, high levels of housing turnover, and high homeownership. Measures of industrialization, immigrant influence and color heterogeneity were not significant. Implications for Brazilian race relations are discussed